Role of adult attachment and spiritual attachment on meaning in life among religious minorities in Thailand: Insights for mental health promotion - Wongratanamajcha, Suriwong; DeMaranville, Justin; Wongpakaran, Tinakon; Permsuwan, Unchalee; Worland, Shirley (Narra J, 2025)
Attachment theory suggests that secure relationships are foundational to meaning in life, but less is known about the role of spiritual attachment, especially among religious minorities. This study examined whether attachment to God mediates the relationship between insecure human attachment and the presence of meaning in life among Thai Protestant Christians. A cross-sectional survey was conducted with Thai Protestant Christians, assessing insecure human attachment (avoidant and anxious), attachment to God, and the presence of meaning in life using validated self-report measures. Mediation analysis was used to test the indirect effect of insecure attachment on meaning via attachment to God. The results showed that attachment to God fully mediated the negative relationship between insecure human attachment and the presence of meaning in life. Participants with higher insecure attachment reported lower meaning in life, but those with a secure attachment to God did not display this deficit. Attachment to God serves as a central psychological resource, a positive figure for humans, and enhances meaning in life, particularly in the minority context of Thai Protestant Christians. These findings highlight the importance of spiritual interventions for individuals experiencing relational or social marginalization.